What is the theoretical and practical framework which shapes the nurse - patient relationship? - Hólmfríður S. Kristjánsdóttir 1959- (1999)
Aim: The aim of this descriptive ethnographic study is to explore culture in one hospital unit in an urban area in Iceland, focussing on the constraints and circumstances experienced by nurses and especially regarding patient-oriented nursing. The Research question: What is the theoretical and practical framework which shapes the nurse-patient relationship in a medical unit in urban area in Iceland? Method: The approach I used toward answering this research question is ethnographic, but I did participant observation and wrote extensive field notes at the medical unit; furthermore, I intensively interviewed one female nurse, my key informant, applying a mixture of semi-structured and in-depth interviewing as a data collection method. Data analyses: My data was analysed according to the Ethnonursing Data Analysis Model developed by Leininger (1991). Findings: The findings and themes emerging from my research strongly suggest that there are severe and considerable constrains within hospital culture against the nurses’ ability to be ´patient-oriented`. According to my study the central, critical issues are time and communication. At the unit where I did my research and between ca. 9:00 and 10:30 nurses had to be, as they expressed it ´at two places at the same time`. I argue and my findings show that this overlap of time hinders the teamwork which is fundamental part of patient-oriented nursing. In order to create and preserve some type of coherence in the hospital culture nurses are socialised into being an oppressed group, individually communicating with other professionals, especially those ranked above them, as subordinates. Hospital culture should be described as dissonant since there seems to be a striking mismatch between espoused values and organisational goals, also because of the competitive spirit between nurses and nursing auxiliaries and the double standard for behaviour, but no formal systems exists for addressing conflict, just an ii informal one. I argue in accordance with the findings of my research ...